EFEKTIVITAS PROGRAM REHABILITASI BERSUMBERDAYA MASYARAKAT TERHADAP PENYANDANG DISABILITAS DENGAN GANGGUAN GERAK - Aditya Denny Pratama; Jihan Syifa Prayudipta (Jurnal Sosial Humaniora Terapan, 2022)
Children with disabilities with movement disorders are losing (in whole or in part) their body functions in motor activities (moving), such as running, fine motor skills, speaking, and others that for their activity daily living and self-care. To help serve people with disabilities, there are programs that are packaged in the form of community-based rehabilitation. This study aims to determine the effectiveness of community-based rehabilitation programs for persons with disabilities with movement disorders. The method used in this research is descriptive qualitative. The results showed that the implementation of the community-based rehabilitation program at Yayasan Pembinaan Luar Biasa Nusantara di Beji, Kota Depok, Jawa Barat, Indonesia was effective in providing education to create independence for persons with disabilities with movement disorders. Effectiveness is based on respondents who meet the inclusion criteria and indicators of the community-based rehabilitation matrix, namely, parents and persons with disabilities can access to health centers, education, and are involved in every activity in the community. The inhibiting factors that affect the effectiveness of the program, namely the lack of teachers or administrators from Yayasan Pembinaan Luar Biasa Nusantara Depok Guidance Foundation who participate in a series of community-based rehabilitation programs are an obstacle.